2013
DOI: 10.1186/1471-2458-13-200
|View full text |Cite
|
Sign up to set email alerts
|

The association between accelerometer-measured patterns of sedentary time and health risk in children and youth: results from the Canadian Health Measures Survey

Abstract: BackgroundSelf-reported screen time is associated with elevated health risk in children and youth; however, research examining the relationship between accelerometer-measured sedentary time and health risk has reported mixed findings. The purpose of this study was to examine the association between accelerometer-measured patterns of sedentary time and health risk in children and youth.MethodsThe results are based on 1,608 children and youth aged 6 to 19 years from the Canadian Health Measures Survey (2007–2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
249
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 225 publications
(318 citation statements)
references
References 32 publications
15
249
1
3
Order By: Relevance
“…bouts of at least 5 or 10 min) is in line with previous studies (Saunders et al, 2013b;Carson et al, 2014;Harrington et al, 2011). In contrast to our finding that sedentary bouts longer than 20 min were rare among children, Colley et al (2013) found that bouts of at least 20, 40, 60, 80, 100 and 120 min were common in 6-19 year old children on weekdays after 3 PM. This contrasting result could be explained by the difference in tolerance minutes that were allowed within sedentary bouts.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…bouts of at least 5 or 10 min) is in line with previous studies (Saunders et al, 2013b;Carson et al, 2014;Harrington et al, 2011). In contrast to our finding that sedentary bouts longer than 20 min were rare among children, Colley et al (2013) found that bouts of at least 20, 40, 60, 80, 100 and 120 min were common in 6-19 year old children on weekdays after 3 PM. This contrasting result could be explained by the difference in tolerance minutes that were allowed within sedentary bouts.…”
Section: Discussionsupporting
confidence: 91%
“…Currently, few epidemiological studies have examined accelerometerbased sedentary bouts and breaks in sedentary time in children (Colley et al, 2013;Carson and Janssen, 2011;Carson et al, 2014;Harrington et al, 2011;Saunders et al, 2013b). Although all these studies used similar accelerometer-based data (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations